Effects of switching diet formulations on finishing pig performance - Potter, M. L.; Tokach, Michael D.; DeRouchey, Joel M.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 1,239 finishing pigs (initially 43 lb) were used in a 41-d trial to determine the effects on ADG, ADFI, and F/G of switching every 2 wk from a corn-soybean mealbased diet to a diet containing alternative ingredients. Pens of pigs were weighed and allotted randomly to 1 of 4 dietary treatments. Dietary treatments were: (1) feeding a corn-soybean meal-based diet; (2) feeding an alternative ingredient-based diet; (3) feeding both diets in succession by feeding 2 wk of the corn-soybean meal-based diet followed by 2 wk of the diet with alternative ingredients, then feeding the corn-soybean meal-based diet again for 2 wk (Switch 1); or (4) feeding both diets in succession by feeding 2 wk of the diet with alternative ingredients followed by 2 wk of the cornsoybean meal-based diet, then feeding the diet with alternative ingredients again for 2 wk (Switch 2). Nutrient specifications of the corn-soybean meal-based diet and alternative ingredient-based diet were similar within phase, and diets were fed in 2 phases (Phase 1: 4 wk, and Phase 2: 2 wk). Pigs were weighed and feed intake was recorded by pen on d 0, 13, 27, and 41 to determine ADG, ADFI, and F/G. Although performance among pigs fed the different dietary treatments was variable throughout the testing periods, dietary treatment did not affect (P ≥ 0.07) overall ADG or ADFI. This resulted in pigs being of similar (P = 0.41) off-test weight, regardless of the diet (corn-soybean meal-based or alternative ingredient-based diets) or diet sequence (Switch 1 or Switch 2). Therefore, in this study with diets formulated to similar nutrient specifications but having different ingredients, pigs had comparable performance regardless of whether a corn-soybean meal-based diet or an alternative ingredient-based diet was fed continuously or whether pigs were fed these same 2 diets alternated every 2 wk.
Keywords: Swine; Alternative ingredients; Diet formulation; Diet switching